The effectiveness and challenges of online learning for secondary school students: a case study / Zulaikha Mohd Basar … [et al.] - Mohd Basar, Zulaikha; Mansor, Azlin Norhaini; Jamaludin, Khairul Azhar; Alias, Bity Salwana (Universiti Teknologi MARA, 2021)
The COVID-19 pandemic has forced an immediate implementation of online learning. However, little is known about its effectiveness and challenges faced by the students. Thus, this study is aimed at examining the effectiveness of online learning and the challenges that it presents to pupils’ abilities to learn. This study employed a case study design using a survey questionnaire, administered to 99 students from a secondary school in Jasin, Melaka. Data were analysed descriptively (calculation of percentage and frequency). Generally, the findings indicated that the students have computers or smartphones and an internet connection at home. Besides, it was found that that the ability and comfort ability to use computers was high (>93%). However, their motivation in online learning was low (41.5%) and ability to work in a group was at a moderate level (66.7%). They also agreed that conventional teaching (face-to-face) was important for their learning (98%). These findings are valuable for the government, school administrators, teachers and parents to acknowledge the importance of well-equipped facilities and a stable internet connection for effective learning. However, it is recommended for future researchers to utilize a larger sample size and students from various backgrounds to better understand this issue.